Turkey and Its Position on the Cyprus Question Since 1974 - OSIEWICZ, PRZEMYSŁAW (Rocznik Integracji Europejskiej, 2013)
The Cyprus question is one o f the most complex international disputes, which the Republic of Turkey has been engaged in since its foundation in 1923. Although Cyprus was conquered by the Ottoman Empire in 1571, the Turks actually lost control over the island in 1878. British rule only strengthened ethnic divisions in Cyprus, especially when Cyprus became a Crown Colony in 1925. After World War II, Greek Cypriots wanted to unite with mainland Greece (enosis), while Turkish Cypriots promoted the division o f the island’s territory between Greece and Turkey (taksim). Finally, both sides agreed on the foundation o f an independent Cypriot state, named the Republic of Cyprus, in 1960, and became its guarantors. Yet this was not the end of the Cyprus question. Lack of mutual trust led to further clashes between the two communities in 1963 and resulted in a disintegration of the state. The most important events, however, took place in 1974, when Turkey decided to intervene militarily on the island in response to a Greek Cypriot coup d ’etat. This paper is devoted to the Turkish position on the Cyprus question after the intervention and division o f Cyprus. Has the policy undergone any significant changes since 1974? Is the Cyprus question a matter of Turkish national interest? The paper compares two periods, namely that from 1974 to 2002 and after 2002.